2022
DOI: 10.3390/ijerph191811418
|View full text |Cite
|
Sign up to set email alerts
|

The Level of COVID-19 Anxiety among Oncology Patients in Poland

Abstract: Cancer patients tend to have a high psychological burden. Half of cancer patients suffer from severe affective disorders and anxiety disorders, while one-third struggle with mild forms of these. The COVID-19 pandemic is damaging the mental health of the population due to social restrictions. A growing number of studies note the role of COVID-19 anxiety in the health and quality of life of cancer patients. The purpose of this study is to estimate the level of COVID-19 anxiety among oncology patients and to test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…Different studies showed that cancer patients had experienced a higher level of stress, anxiety and depression to receive health services when compared to non-cancer patients with the onset of Covid-19 (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Different studies showed that cancer patients had experienced a higher level of stress, anxiety and depression to receive health services when compared to non-cancer patients with the onset of Covid-19 (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, according to a study by Kim et al [ 39 ], in the COVID-19 pandemic, patients with cancer experienced depression and anxiety about the viral pandemic and disruption to their access to healthcare services, which may have adversely affected their mental health and led to behavioral disorders. The studies of Vicinanza et al [ 10 ] and Grajek et al [ 11 ], highlights the presence of anxiety in the cancer patients undergoing radiotherapy during the pandemic of COVID-19. Also, the findings of previous studies showed that the side effects of chemotherapy can cause psychosocial damage such as pain, depression, insomnia and anxiety in patients [ 40 , 41 ] and during the epidemic of Covid-19, consequently increased psychological pressure due to COVID-19, was increased the level of these psychological damages [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…[10] and Grajek et al [11], highlights the presence of anxiety in the cancer patients undergoing radiotherapy during the pandemic of COVID-19. Also, the findings of previous studies showed that the side effects of chemotherapy can cause psychosocial damage such as pain, depression, insomnia and anxiety in patients [40,41] and during the epidemic of Covid-19, consequently increased psychological pressure due to COVID-19, was increased the level of these psychological damages [42].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations